ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM JAMINAN PELAYANAN KESEHATAN GRATIS DI KABUPATEN BUOL - Mangge, Abdullah AS. (Katalogis, 2013)
The Purposes of this research are to give the understanding about the form and process ofÂ free healthy program and to analyze the implementation of Buol Regent Regulation Policy No.05 Year 2010 about Free Healthy Service Guarantee System in Buol Region. The research was carried out at Regional Public Hospital Buol Region as the hospital of patients reconciliation which wasÂ from 11 local government clinics spread in Buol Region. Whereas the technique of data collection was done through observation, deep interview, and documentation. All data will be inventorized and proceeded and analyzed using qualitative descriptive data analysis.Deal with the research result, that the implementation of free healthy service guarantee from Regent Regulation No. 5 Year 2010 was not effective to the public interest level, at least there were some factors that influenced the implementation of the policy namely; content of policy which consisted of interest affected, types of benefis, extent change of envisioned and resources commited. In relation to the content of policy, intended to be through politics manipulation process, so that it could give benefit to the executor. This is one of the indicators that indicated the unsuccessful implementation of the policy, because public gets difficulty and unsatisfaction to have free healthy facility as assigned by the regulation. Therefore, the service generallly did not give positive impact to the public. Finally, it can be stated that the Grindle theory is still applicable and relevant to be used in the field.